International aid and financial crises in donor countries - Dang, Hai-Anh (The World Bank, 2010)
The global financial crisis has already led to sharp downturns in the developing world. In the past, international aid has been able to offset partially the effects of crises that began in the developing world, but because this crisis began in the wealthy countries, donors may be less willing or able to increase aid in this crisis. Not only have donor-country incomes fallen, but the cause of the drop - the banking and financial-sector crisis - may exacerbate the effect on aid flows because of its heavy fiscal costs. This paper estimates how donor-country banking crises have affected aid flows in the past, using panel data from 24 donor countries between 1977 and 2007. The analysis finds that banking crises in donor countries are associated with a substantial additional fall in aid flows, beyond any income-related effects, perhaps because of the high fiscal costs of crisis and the debt hangover in the post-crisis periods. In most specifications, aid flows from crisis-affected countries fall by an average of 20 to 25 percent (relative to the counterfactual) and bottom out only about a decade after the banking crisis hits. In addition, the results confirm that donor-country incomes are robustly related to per-capita aid flows, with an elasticity of about 3. Because all donor countries are being hit hard by the current global recession, and several have also suffered banking-sector crises, there are reasons to expect that aid could fall by a significant amount (again, relative to the counterfactual) in the coming years - just when aid may be most clearly justified to help smooth exogenous shocks to developing countries